Tick-borne flaviviruses antagonize both IRF-1 and type I interferon signaling to inhibit dendritic cell function - Robertson, Shelly J. (2014)
Tick-borne encephalitis virus (TBEV), a member of the Flaviviridae family, is a leading cause of viral encephalitis in Europe and Asia. Dendritic cells (DCs), as early cellular targets of infection, provide an opportunity for flaviviruses to inhibit innate and adaptive immune responses. Flaviviruses modulate DC function, but the mechanisms underpinning this are not defined. We examined the maturation phenotype and function of murine bone marrow-derived DCs infected with LGTV, a naturally attenuated member of the TBEV serogroup. LGTV infection failed to induce DC maturation or a cytokine response. Treatment with LPS or LPS/IFNγ, strong inducers of inflammatory cytokines, resulted in enhanced TNFα and IL-6 production, but suppressed IL-12 production in infected DCs compared to uninfected "bystander" cells or mock-infected controls. LGTV-mediated antagonism of type I IFN (IFN-I) signaling contributed to inhibition of IL-12p40 mRNA expression at late time-points following stimulation. However, early suppression was still observed in DCs lacking the IFN-I receptor (Ifnar(−/−)) suggesting that additional mechanisms of antagonism exist. The early IFN-independent inhibition of IL-12p40 was nearly abolished in DCs deficient in interferon regulatory factor-1 (IRF-1), a key transcription factor required for IL12 production. LGTV infection did not affect Irf-1 mRNA expression, but rather diminished IRF-1 protein levels and nuclear localization. The effect on IRF-1 was also observed in DCs infected with the highly virulent Sofjin strain of TBEV. Thus, antagonism of IRF-1 is a novel mechanism that synergizes with the noted ability of flaviviruses to suppress IFNAR-dependent signaling, resulting in the orchestrated evasion of host innate immunity.